2015
DOI: 10.1016/j.procbio.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and stability of bovine serum albumin (BSA) using cholinium-based Good's buffers ionic liquids

Abstract: Good's buffers ionic liquids (GB-ILs), composed of cholinium-based cations and Good's buffers anions, display self-buffering characteristics in the biological pH range, and their polarity and hydrophobicity can be easily tuned by a proper manipulation of their ions chemical structures. In this work, the extraction ability for bovine serum albumin (BSA) of aqueous biphasic systems (ABS) formed by polypropylene glycol 400 (PPG 400) and several GB-ILs was evaluated. ABS formed by PPG 400 and cholinium chloride ([… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 63 publications
4
67
0
1
Order By: Relevance
“…For example, Kumar and Venkatesu have observed that some short-chain alkyl imidazolium-based and ammonium-based ILs stabilize insulin [12,13]. High-yield extraction of proteins, antibodies and enzymes and at the same time their preserved native or active conformation in cholinium-based ionic liquid buffers have also been reported [14,15]. The effect of 1-ethyl-3-methyl-imidazolium-based ILs as refolding additives and suppressors of protein aggregation have been estimated for cardioactive peptides, lysozyme, recombinant plasminogen activators, antibody fragments, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kumar and Venkatesu have observed that some short-chain alkyl imidazolium-based and ammonium-based ILs stabilize insulin [12,13]. High-yield extraction of proteins, antibodies and enzymes and at the same time their preserved native or active conformation in cholinium-based ionic liquid buffers have also been reported [14,15]. The effect of 1-ethyl-3-methyl-imidazolium-based ILs as refolding additives and suppressors of protein aggregation have been estimated for cardioactive peptides, lysozyme, recombinant plasminogen activators, antibody fragments, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, polymer/salt‐based ABS using cholinium ([Ch] + )‐based salts (or ionic liquids, ILs) were proposed as platforms for solutes partition, particularly, due to the relative hydrophobicity/hydrophilicity balance between the coexisting phases . Furthermore, it was demonstrated that [Ch] + ‐based salts can promote specific protein‐ions interactions, acting directly on the protein partitioning capacity, as shown for beta‐lactoglobulin, A and B, lysozyme, and ribonuclease A and B, as well as on protein stabilization, as previously observed for monoclonal antibodies, cytochrome c, rubisco, bovine serum albumin (BSA) and α‐chymotrypsin …”
Section: Introductionmentioning
confidence: 65%
“…O pigmento a ser separado e as demais proteínas presentes no meio podem interagir através de ligações de hidrogênio, forças dispersivas ou interações eletrostáticas (Taha et al, 2015). Desta forma, considerando-se os fatores de purificação para ambos os sistemas, percebe-se que apesar do pigmento migrar majoritariamente para a fase contendo LI, não foi possível que houvesse boa separação de outras proteínas e dos demais contaminantes.…”
Section: Ufscar -São Carlos -Sp 16 a 19 De Julho De 2017unclassified